HUBUNGAN DISIPLIN KERJA DAN MOTIVASI KERJA DENGAN KINERJA GURU MAN SE-BANDAR LAMPUNG - Arif, Bustanul (Managere: Indonesian Journal of Educational Management, 2021)
This study aims to determine the relationship between work discipline and work motivation with the performance of MAN teachers in Bandar Lampung. This type of research is associative quantitative with a total population of 164 teachers and a research sample of 63 teachers. The data collection technique used a questionnaire. The data were analyzed using simple linear regression analysis and multiple linear regression analysis using IBM SPSS Statistics 23. The results showed that work motivation have a significant relationship with teacher performance. Judging from the value of the coefficient of determination of 0.550, the results show that the contribution or contribution of the relationship between X1 work discipline and X2 work motivation with Y teacher performance is 55% while the remaining 45% is the contribution of other variables not included in the study.